2022
DOI: 10.1029/2021ef002621
|View full text |Cite
|
Sign up to set email alerts
|

Multisector Dynamics: Advancing the Science of Complex Adaptive Human‐Earth Systems

Abstract: The broader global community is navigating evolving climate risks, rapid energy transitions, and the growing recognition that sustainable future pathways will require fundamental transformations in our collective management of socio-environmental systems (de Vos et al.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 113 publications
0
64
0
Order By: Relevance
“…Energy transitions in socio‐economic systems will involve complex interactions among sectors, which are intricately linked through trade (the output of one sector is often the input to other sectors) and infrastructure, as well between human and Earth systems as society attempts to achieve long‐term climate goals. The relatively new field of MultiSector Dynamics (MSD) has recognized the need to develop a deeper understanding of the interactions, interdependencies and coevolution of sectors and systems, and has embraced uncertainty analysis and quantification as a research priority toward the goal of providing information relevant for decision‐making (Moss et al., 2016; Reed, Hadjimichael, Moss, Brelsford, et al., 2022, Reed, Hadjimichael, Moss, Monier, et al., 2022). In that vein, we seek to quantify socioeconomic uncertainties, employing a multi‐sector, multi‐region model of the world economy that captures the cross‐sectoral impacts of energy transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Energy transitions in socio‐economic systems will involve complex interactions among sectors, which are intricately linked through trade (the output of one sector is often the input to other sectors) and infrastructure, as well between human and Earth systems as society attempts to achieve long‐term climate goals. The relatively new field of MultiSector Dynamics (MSD) has recognized the need to develop a deeper understanding of the interactions, interdependencies and coevolution of sectors and systems, and has embraced uncertainty analysis and quantification as a research priority toward the goal of providing information relevant for decision‐making (Moss et al., 2016; Reed, Hadjimichael, Moss, Brelsford, et al., 2022, Reed, Hadjimichael, Moss, Monier, et al., 2022). In that vein, we seek to quantify socioeconomic uncertainties, employing a multi‐sector, multi‐region model of the world economy that captures the cross‐sectoral impacts of energy transitions.…”
Section: Introductionmentioning
confidence: 99%
“…To address interdependencies between sectors, multisector dynamics (MSD) frames the study of interacting sectors as that of a “systems of systems,” acknowledging that the vulnerability, risk, and resilience of any given sector is nearly always intertwined with that of many others (Haimes, 2018; Reed et al., 2022). Such a view of sectors and their interactions calls for a complex adaptive systems approach for the understanding of cross‐sectoral interactions and the role of humans therein (Moss et al., 2016).…”
Section: Introduction—modeling the Complexity Of Multisector Dynamicsmentioning
confidence: 99%
“…The water scarcity analysis we conduct in this study is rooted in an explicit characterization of global multisector dynamic interactions across systems and scales (Reed et al., 2022), including within LAC. Most research on the future of water in Latin America has not taken a multisector, multi‐scale approach (DeVincentis et al., 2021), though previous studies have demonstrated the importance of this style of analysis (Santos Da Silva et al., 2019; Wild, Khan, Zhao, et al., 2021), particularly given the strong linkages between the region's water and land systems.…”
Section: Introductionmentioning
confidence: 99%